STUDY EFFECT OF SOME FIELD FACTORS IN DETERMINING THE PERFORMANCE AGRICULTURAL TRACTOR - Ghazwan, A. Dahham (Mesopotamia Journal of Agriculture)
This research was conducted to study the effect of three levels of soil moisture content (10-13%),(14-17%),(18-21%) with two plowing depths by using the disk plow(10-15cm),(15-20cm) and three different speeds (3.5, 5.5, 7.5 km/hr.) on Slippage percentage, Mobility number, Motion resistance,Motion resistance ratio and tractive efficiency. Split split plot design and randomized complete block design with three replications were used in this experiment. Results showed that the effect of  soil moisture content was significant in all studied characteristics, Soil moisture content (14-17%) recorded highest value of mobility number(67.83) and highest tractive efficiency (77.51), while Soil moisture content (18-21%) recorded highest slippage percentage (14.06%) and highest motion resistance(1.40 KN) and highest motion resistance ratio(6.37%).It was found that plowing depths had a significant in all the studied characteristics, The increased of plowing depths from (10-15cm) to (15-20cm) increased slippage percentage and motion resistance and motion resistance ratio , and lower of mobility number and tractive efficiency. Also it was found that speeds had a significant in all studied characteristics, The increased of speeds from(3.5 km/hr.) to (5.5km/hr.) to(7.5km/hr.) increased slippage percentage and motion resistance and motion resistance ratio, and lower of mobility number and tractive efficiency. All of  interaction soil moisture content, plowing depths and speeds had a significant in all the studied characteristics. Results showed that the tractive efficiency and mobility number of two-wheel drive (2WD) tractors are clearly influenced by field factors (soil moisture content and plowing depths) and condition tractor (speed and draft force required to pull agricultural machine in the field and motion resistance of the tractor tires and slippage). The tractive efficiency is clearly affected by mobility number of the tractors.